Bush imperator : guerre du Golfe et "nouvel ordre mondial" - Jaber, Salah; Jaber, Salah; Serfaty, Abraham; Warshawski, Michel; Weksler, Marcello (Montreuil : La Brèche, 1991)
Bibliotheek François Vercammen
Frans
Monografie